Monolithically Integrated μLEDs on Silicon Neural Probes for High-Resolution Optogenetic Studies in Behaving Animals - Wu, Fan; Stark, Eran; Ku, Pei-Cheng; Wise, Kensall D; Buzsáki, György; Yoon, Euisik (Neuron (Cambridge, Mass.), 2015)
We report a scalable method to monolithically integrate microscopic light emitting diodes (μLEDs) and recording sites onto silicon neural probes for optogenetic applications in neuroscience. Each μLED and recording site has dimensions similar to a pyramidal neuron soma, providing confined emission and electrophysiological recording of action potentials and local field activity. We fabricated and implanted the four-shank probes, each integrated with 12 μLEDs and 32 recording sites, into the CA1 pyramidal layer of anesthetized and freely moving mice. Spikes were robustly induced by 60 nW light power, and fast population oscillations were induced at the microwatt range. To demonstrate the spatiotemporal precision of parallel stimulation and recording, we achieved independent control of distinct cells ∼ 50 μm apart and of differential somato-dendritic compartments of single neurons. The scalability and spatiotemporal resolution of this monolithic optogenetic tool provides versatility and precision for cellular-level circuit analysis in deep structures of intact, freely moving animals.